2021
DOI: 10.1016/j.celrep.2021.109398
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity recruits the CRTC1/CREB axis to drive transcription-dependent autophagy for maintaining late-phase LTD

Abstract: Highlights d Neuronal activity recruits autophagy for maintaining NMDARdependent L-LTD d LTD-inducing stimuli are privileged in triggering autophagy gene expression d Excitation-transcription coupling drives autophagy via the CRTC1/CREB axis d The cytoplasm-to-nucleus signaling mediated by CREB and CRTC1 is critical for L-LTD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 72 publications
(130 reference statements)
0
17
0
Order By: Relevance
“…Additionally, Compans et al found that autophagy is required for the degradation of T19-phosphorylated form of PSD95 in NMDAR-LTD induction, which triggers a depletion of PSD95 from synapses and eventually increases short-term plasticity to improve neuronal responsiveness of depressed synapses [ 84 ]. A most recent study has shown that constitutive induction of mTOR-dependent autophagy rescues the prevention of NMDAR-LTD induced by disrupting synergistic action of CREB and CRTC1, two essential transcriptional factors for late-phase long-term synaptic potentiation [ 85 ]. These findings reveal the previously unrecognized functions of autophagy in the regulation of synaptic plasticity and memory (Fig.…”
Section: Autophagy Regulates Presynaptic and Postsynaptic Development And Synaptic Activitymentioning
confidence: 99%
“…Additionally, Compans et al found that autophagy is required for the degradation of T19-phosphorylated form of PSD95 in NMDAR-LTD induction, which triggers a depletion of PSD95 from synapses and eventually increases short-term plasticity to improve neuronal responsiveness of depressed synapses [ 84 ]. A most recent study has shown that constitutive induction of mTOR-dependent autophagy rescues the prevention of NMDAR-LTD induced by disrupting synergistic action of CREB and CRTC1, two essential transcriptional factors for late-phase long-term synaptic potentiation [ 85 ]. These findings reveal the previously unrecognized functions of autophagy in the regulation of synaptic plasticity and memory (Fig.…”
Section: Autophagy Regulates Presynaptic and Postsynaptic Development And Synaptic Activitymentioning
confidence: 99%
“…This role of autophagy in neuronal homeostasis is especially crucial at synapses, which possess high metabolic demands and are vulnerable to accumulated damage and stress (reviewed in ( 15 )). Autophagy has been described to regulate the degradation of several pre- and postsynaptic proteins ( 12 , 5456 ), axonal ER ( 13 ), and synaptic mitochondria ( 14 , 57 ) and, is, thereby, crucial for the regulation of synaptic plasticity, including long-term depression (LTD) ( 11 , 25 , 58 , 59 ). Intriguingly, here we find that ATG5-mediated autophagy does not primarily contribute to the regulation of bulk levels of SV and/or mitochondrial proteins in excitatory or inhibitory neurons i n-vivo .…”
Section: Discussionmentioning
confidence: 99%
“…TORC also acts at least in part by assisting in the recruitment of CBP to CREB. Meanwhile, CREB-regulated transcription coactivator 1(CRTC1) can also dephosphorylate at Ser-151 and is recruited from cytoplasm to the nucleus, where it competes with FXR (fed-state sensing nuclear receptor) for binding to CREB and drives autophagy gene expression (Pan et al, 2021). Some studies have shown that Ca 2+ influx activates CREB through TRPC6, which is an important transcription factor linked to neuronal survival.…”
Section: Nmdar-dependent Neuroprotection In Epilepsymentioning
confidence: 99%